Ateizm i dyskryminacja w obliczu współczesnych zmian na świecie - Łopuszańska, Urszula; Zacharska, Adrianna; Gierszon, Patrycja; Samardakiewicz, Marzena (Kultura-Społeczeństwo-Edukacja, 2020)
The aim of this article is to present the situation of atheists around the world in the face of political and cultural changes in the world due to the increase in religious radicalism, particularly Islamic one, migration and terrorism. The article is of an illustrative character and presents the review of English literature in the scope of the discussed subject matter. Furthermore, the results of the latest global reports on prevalence of atheism in the world and the phenomenon of discrimination against persons not identifying with any faith: atheists, humanists or freethinkers were presented. The results of the selected, recent studies on the social perception of atheists and the phenomena of discrimination against them were shown. Another raised issue was the new social movement called New Atheism widespread mainly in the countries of the Western culture that in the future can constitute a new social and political challenge.